THE INFLUENCE OF LIQUIDITY AND COMPANY SIZE ON STOCK PRICES IN 2019-2023 - Muadz Zaki Mudzakir; Intan Pramesti Dewi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to further examine the effect of liquidity and company size on stock prices, with the hope of contributing to the literature and becoming a reference for investors in making better investment decisions. This study is a quantitative study and uses descriptive and verification methods to provide a clear and systematic picture of the data and facts observed, so that it can provide a deep understanding of the characteristics of the variables studied. The results of the study indicate that liquidity has a positive but insignificant effect on stock prices and company size has a significant positive effect on stock prices. It can be concluded that companies with larger total assets tend to have higher stock prices, which can be interpreted as an indicator of investor confidence in the stability and prospects of the company in the future, so that it will affect stock prices.